2010
DOI: 10.1242/dev.038554
|View full text |Cite
|
Sign up to set email alerts
|

Repression of zygotic gene expression in theXenopusgermline

Abstract: SUMMARYPrimordial germ cells (PGCs) in Xenopus are specified through the inheritance of germ plasm. During gastrulation, PGCs remain totipotent while surrounding cells in the vegetal mass become committed to endoderm through the action of the vegetal localized maternal transcription factor VegT. We find that although PGCs contain maternal VegT RNA, they do not express its downstream targets at the mid-blastula transition (MBT). Transcriptional repression in PGCs correlates with the failure to phosphorylate ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(108 citation statements)
references
References 75 publications
(89 reference statements)
5
103
0
Order By: Relevance
“…3 B-N and Fig. S5 A-C), as reported (21,22). The germ plasm was identified by its enrichment in mitochondria, besides the localization of vegt transcripts and protein (Fig.…”
Section: Resultssupporting
confidence: 69%
“…3 B-N and Fig. S5 A-C), as reported (21,22). The germ plasm was identified by its enrichment in mitochondria, besides the localization of vegt transcripts and protein (Fig.…”
Section: Resultssupporting
confidence: 69%
“…Using isolated PGCs as a point of entry, Venkatarama et al (2010) showed that transcriptional activity in Xenopus PGCs is repressed, relative to somatic cells, from mid-blastula through neurula stages, coinciding with the interval during which somatic germ layers are specified. Consequently, as in Caenorhabditis elegans and Drosophila, transcriptional repression prevents specification of the nascent germ line to a somatic fate.…”
Section: Preformationmentioning
confidence: 99%
“…As a result, the PGC progenitors must repress the cell-autonomous effects of maternally encoded transcription factors, in addition to repressing the response to external stimuli. For example, in Xenopus embryos, germ plasm counters the potential effects of VegT, which is an endodermal determinant whose RNA is also localized to the vegetal hemisphere and inherited by the PGCs (Venkatarama et al 2010). However, VegT is not localized in oocytes of axolotls (Nath & Elinson 2007), or even basal species of fish (H Chen, M Loose and A D Johnson, unpublished observations), raising the possibility that the evolution of germ plasm, generally, is a precondition for the evolution of a mosaic distribution of somatic determinants.…”
Section: Preformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable integration frequencies were improved 20-fold by incorporation of an attB site in the transgene plasmid and expression of ϕC31 integrase to promote chromosomal integration (8). The apparently low frequencies of stable integration may be due to transcriptional repression of the integrated transgenes by the genome-wide epigenetic modifications present in the PGCs of many organisms (9)(10)(11)(12).…”
mentioning
confidence: 99%